Mechanisms by Which Obesity Promotes Acute Graft-Versus-Host Disease in Mice - Khuat, Lam T.; Vick, Logan V.; Choi, Eunju; Dunai, Cordelia; Merleev, Alexander A.; Maverakis, Emanual; Blazar, Bruce R.; Monjazeb, Arta M.; Murphy, William J. (Frontiers in Immunology, 2021)
The efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT) is limited by the occurrence of acute and chronic graft-versus-host disease (GVHD). We have recently demonstrated that obesity results in exacerbated acute gastrointestinal GVHD in both mouse models and clinical outcomes due to increased pro-inflammatory cytokine responses and microbiota alterations. We therefore wanted to delineate the role of the various parameters in obesity: adiposity, effects of high-fat (HF) diet and the role of microbiome on GVHD pathogenesis by taking advantage of a mouse strain resistant to diet-induced obesity (DIO). Female BALB/c mice are resistant to DIO phenotype with approximately 50% becoming DIO under HF diets. The DIO susceptible recipients rapidly succumb to acute gut GVHD whereas the DIO resistant recipient littermates, which do not become obese, are partially protected from GVHD indicating that being on HF diet alone contributes to but is not the primary driver of GVHD. Microbiome assessment revealed restricted diversity in both cohorts of mice but coprophagy normalizes the microbiota in mice housed together. We then individually housed DIO-resistant, DIO-susceptible and lean control mice. Notably, each of the individually housed groups demonstrates marked restricted diversity which has been shown to occur from the stress of single housing. Despite the restricted microbiome diversity, the GVHD pathogenesis profile remains consistent to the group-housed mice with the lean control single-housed mice exhibiting no acute GVHD and DIO-resistant recipients showing again partial protection. These results demonstrate that the deleterious effects of obesity on acute gut GVHD are critically dependent on adiposity with the HF diet also playing a lesser role, and the microbiome alterations with obesity instead appear fuel ongoing acute GVHD processes.